Multi-physical field null medium: new solutions for the simultaneous control of EM waves and heat flow - Sailing He; Ruili Zhang; Junbo Liang (Opto-Electronic Advances)
In a recent study, a research group from Taiyuan University of Technology published their findings in the journal Opto-Electronic Science with a title "Simultaneously realizing thermal and electromagnetic cloaking by multi-physical null medium." This work introduces a structure that can control simultaneously both electromagnetic waves and heat flow. For the first time, a single structure capable of cloaking both electromagnetic waves and heat flow was experimentally demonstrated. This research offers new solutions for the simultaneous control of electromagnetic waves and heat flow, and advances the hybrid design of electromagnetic compatibility and thermal management, which may have important potentials in e.g. medical applications.